Mathematical Understanding Ability To Solve The Word Problem - Mayasri, Dian; Purwanty, Ratna; Monika, Santy (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study aims to describe the ability of students to mathematical understanding a solved word problem. The study subjects were 28 grade VII students of Junior High School. Data collection techniques were carried out in the form of tests of students' abilities in mathematical understanding and unstructured interviews. The test used to measure the ability to understand the concept is in the form of description questions as many as 4 questions with integer operation material on the story problem. The results of this study indicate that students' mathematical understanding with a high category is 17%, the medium category is 10%, and low category is 73%.